Implementation of Case-Based Method (CBM) Learning Model under OBE paradigm in the Electromagnetic Field Course - Abdul Rajab; Baharuddin Baharuddin (Edumaspul: Jurnal Pendidikan, 2024)
This paper evaluates the implementation of the Case-Based Learning Model (CBM) in the Electromagnetic Field course under the Outcome-Based Education (OBE) approach in the undergraduate Electrical Engineering program at Universitas Andalas (Unand). CBM, involving students in case analysis, is integrated into OBE to achieve desired learning outcomes. Evaluation is conducted through attendance, mid-term exams (UTS), final exams (UAS), and case study reports. The analysis of student grades shows satisfactory class performance but with significant variability. Improvement focus is recommended on enhancing conceptual understanding, especially prior to UTS and UAS. By focusing on strengthening conceptual understanding and intervening with low-performing students, this model can continue to enhance the quality of learning in the Electromagnetic Field course. This evaluation provides in-depth insights into individual achievements and class dynamics overall. In conclusion, the implementation of CBM in Electromagnetic Field within the OBE framework provides opportunities to produce graduates with relevant theoretical knowledge and practical skills.